Impact of Resected Gastric Volume on Postoperative Weight Loss after Laparoscopic Sleeve Gastrectomy. (1st December 2019) - D'Ugo, Stefano; Bellato, Vittoria; Bianciardi, Emanuela; Gentileschi, Paolo
Abstract : Among the bariatric surgery community, it has recently emerged the idea of a possible association between resected gastric volume (RGV) and weight loss after laparoscopic sleeve gastrectomy (LSG). If the size of the sleeve depends on the bougie caliber, the resected volume of the stomach remains something which is not possible to standardize. The aim of the study was to investigate a possible relationship between RGV and weight loss after LSG. We developed a mathematical method to calculate the RGV, based on the specimen size removed during LSG. Ninety-one patients (63 females and 28 males) affected by morbid obesity were included in the study. They underwent LSG between 2014 and 2016. Mean preoperative BMI was 45 ± 6.4 . At 1 year after LSG, the mean BMI was 30 ± 5.3 and the EWL% was 65 ± 20.2 . The statistical analysis of RGV, BMI, and EWL% at 1-year follow-up did not find any correlation between the volume of stomach removed and the weight loss after LSG. Further studies in the future should clarify the potential role of RGV during LSG. This trial is registered with ClinicalTrials.gov NCT03938025 .